2018
DOI: 10.1039/c8nj01312h
|View full text |Cite
|
Sign up to set email alerts
|

Selective recognition of atropine in biological fluids and leaves ofDatura stramoniumemploying a carbon nanotube–chitosan film based biosensor

Abstract: This paper demonstrates a selective, expeditious and facile electrochemical approach for the ultrasensitive detection of atropine in complex matrices.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 46 publications
2
10
0
Order By: Relevance
“…The n value estimated was 1.898, indicating that two electron per molecule are involved in the oxidation of scopolamine. Hence, based on these results and according to others works for similar compounds [33][34][35] the proposed oxidation mechanism of scopolamine is shown in Scheme SM1.…”
Section: Electrochemical Behavior Of Scopolamine On Ms-cpessupporting
confidence: 65%
“…The n value estimated was 1.898, indicating that two electron per molecule are involved in the oxidation of scopolamine. Hence, based on these results and according to others works for similar compounds [33][34][35] the proposed oxidation mechanism of scopolamine is shown in Scheme SM1.…”
Section: Electrochemical Behavior Of Scopolamine On Ms-cpessupporting
confidence: 65%
“…Their work also demonstrates long time‐span stability over 7 days for the atropine sensors, which can be attributed to chitosan's excellent gel‐forming ability and nontoxicity. Similar research on chitosan‐nanocomposite based electrochemical sensors also demonstrated that chitosan nanocomposite materials can acquire addition chemo‐physical properties from different nanomaterials such as specificity to atropine from SWCNT‐chitosan and to dopamine from graphite‐chitosan composite . Together with nanomaterials, conductive polymer such as polypyrrole can also be added into chitosan nanocomposite for improved conductivity in such enzyme‐free sensors.…”
Section: Recent Developmentsmentioning
confidence: 79%
“…Mane et al. reported an atropine biosensor based on single walled carbon nanotube (SWCNT)‐chitosan film on glassy carbon electrode, in which chitosan was used as a dispersion matrix and stabilizer . Uniform dispersion of SWCNTs in chitosan is realized through covalent attachment, which is verified byFTIR and Raman spectra.…”
Section: Recent Developmentsmentioning
confidence: 97%
“…Compared with curve (a), in addition to the appearance of the oxidation peak of L-HSM (peak potential of 0.741 V), a new oxidation peak appears at 0.879 V. The potential difference (ΔE p ) between this peak and the L-HSM oxidation peak is 0.138 V. This peak is presumed to be the oxidation peak of D-HSM in ATP according to a previous report. 48 In addition, the oxidation peak of L-HSM in curve (b) is slightly higher than that of D-HSM, which is attributed to the incomplete racemization of L-HSM in ATP. On NIP/CuFeS 2 /C/GCE, both L-HSM (curve c) and ATP (curve d) show weak peak current densities, and both show only one oxidation peak for L-HSM.…”
Section: Electrochemical Characterization Of Modified Electrodesmentioning
confidence: 94%